1997
DOI: 10.7547/87507315-87-10-466
|View full text |Cite
|
Sign up to set email alerts
|

1997 William J. Stickel Bronze Award. Comparison of strategies for reducing pressure at the site of neuropathic ulcers

Abstract: Few scientific data are available on the effectiveness of commonly used modalities for reducing pressure at the site of neuropathic ulcers in persons with diabetes mellitus. The authors' aim was to compare the effectiveness of total contact casts, half-shoes, rigid-soled postoperative shoes, accommodative dressings made of felt and polyethylene foam, and removable walking casts in reducing peak plantar foot pressures at the site of neuropathic ulcerations in diabetics. Using an in-shoe pressure-measurement sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 15 publications
2
90
1
Order By: Relevance
“…The nonremovable TCC and the RCC were similar in many aspects, and earlier studies did not show a difference in pressure relief between these two modalities (30,31). As suggested earlier (32), part of the efficacy of the nonremovable TCC is possibly related to the "forced compliance" for off-loading.…”
Section: Nabuurs-franssen and Associatesmentioning
confidence: 50%
“…The nonremovable TCC and the RCC were similar in many aspects, and earlier studies did not show a difference in pressure relief between these two modalities (30,31). As suggested earlier (32), part of the efficacy of the nonremovable TCC is possibly related to the "forced compliance" for off-loading.…”
Section: Nabuurs-franssen and Associatesmentioning
confidence: 50%
“…This applies, in particular, to TCC [15][16][17]. Peak pressure was also significantly reduced in a bi-valved total contact cast and the Aircast walker compared to a control shoe (p < 0.01) [12].…”
Section: Foot Offloading and Postural Stabilitymentioning
confidence: 77%
“…Removable walkers were shown to be as effective as TCCs and more effective than forefoot offloading shoes and extra-depth shoes in reducing forefoot peak pressures [87,88]. Forefoot offloading shoes were found to be more effective than accommodative felt and foam dressings (worn in a post-operative shoe) or post-operative shoes alone [87]. The heel region was found to be best offloaded with a TCC, followed by removable walkers, which, in turn, were more effective than depth-inlay shoes [86].…”
Section: Other Offloading Interventionsmentioning
confidence: 99%
“…However, five uncontrolled studies on this topic were identified [86][87][88][89][90]. TCCs appear to offload the affected extremity effectively.…”
Section: Plantar Pressure Reductionmentioning
confidence: 99%